2008
DOI: 10.2172/944124
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling Studies of The Dissolution-Diffusion-Convection ProcessDuring CO2 Storage in Saline Aquifers

Abstract: For purposes of geologic storage, CO2 would be injected into saline formations at supercritical temperature and pressure conditions, and would form a separate phase that is immiscible with the aqueous phase (brine). At typical subsurface temperature and pressure conditions, supercritical CO2 (scCO2) has lower density than the aqueous phase and would experience an upward buoyancy force. Accordingly, the CO2 is expected to accumulate beneath the caprock at the top of the permeable interval, and could escape from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 18 publications
5
97
0
Order By: Relevance
“…Numerical studies of brine convection (Pruess and Zhang 2008) using much finer grid resolution than this study indicate that the details of convection (e.g., how many convection Fig. 19 East-west cross-section of the dissolved CO 2 plume at a series of times for sensitivity-study Case SH4, shown by plotting X CO 2L , mass fraction of CO 2 in the aqueous phase, in the plane y = 0.…”
Section: Shale Vertical Permeability Studiesmentioning
confidence: 81%
See 2 more Smart Citations
“…Numerical studies of brine convection (Pruess and Zhang 2008) using much finer grid resolution than this study indicate that the details of convection (e.g., how many convection Fig. 19 East-west cross-section of the dissolved CO 2 plume at a series of times for sensitivity-study Case SH4, shown by plotting X CO 2L , mass fraction of CO 2 in the aqueous phase, in the plane y = 0.…”
Section: Shale Vertical Permeability Studiesmentioning
confidence: 81%
“…For a typical CO 2 diffusivity of D = 2 . 10 −9 m 2 /s (Pruess and Zhang 2008), the characteristic diffusion length (Dt) 1/2 is only 0. 5 m for 4 years, 2.5 m for 100 years, and 8 m for 1,000 years, all small compared to CO 2 plume dimensions.…”
Section: Numerical Simulatormentioning
confidence: 99%
See 1 more Smart Citation
“…The top boundary is saturated with dissolved CO 2 . The configuration is widely used for validation and comparison of CO 2 -sequestration modeling (Pruess and Zhang 2008;Pau et al 2010;Allen and Sun 2012).…”
Section: Resultsmentioning
confidence: 99%
“…With this configuration and concentration on the top boundary constant over time, the quantity of CO 2 that diffuses into the underlying fluid can be computed analytically with a complementary error function (Pruess and Zhang 2008;Clark 2009;Allen and Sun 2012). With this function, the concentration with distance y from the boundary at time t can be evaluated as…”
Section: Resultsmentioning
confidence: 99%